Effects of Rhus typhina Invasion on Soil Physicochemical Properties and Carbon Emissions in Urban Green Spaces - Wang, Zihan; Wu, Junjie; Zhang, Dan; Gong, Chao; Wang, Qiong; Zhai, Chang; Dai, Xinzhu (Forests, 2022)
Alien plants invasion have become a hot issue in the field of ecology. The invasion of alien plants is usually accompanied by changes in the physical and chemical properties of the soil, the ensuing negative feedback creates a favorable environment for its own growth and expansion. Invasive plans have a strong ability to sequester carbon, which can greatly affect the original local ecological environment. In this study, we selected Rhus typhina, an invasive plant widely used for greening, as the experimental subject and natural growing grassland as the control. The aims were to investigate the effects of different degrees of invasion of R. typhina on soil physicochemical properties and carbon emissions, and to explore the influential factors on carbon emission. The results showed that R. typhina invasion significantly increased soil pH, total nitrogen content, easy extraction of glomalin-related soil protein (EEG) and cumulative CO2 emissions (CEM). It is worth noting that the CEM increased significantly during the severe invasion by R. typhina. The significant increase in soil NH4+-N content and the decrease in soil NO3−-N content indicate that the soil after the invasion of R. typhina has better uptake of NH4+-N. Temperature and soil moisture content had significant direct effects on CEM, while NH4+-N, NO3−-N, EEG and temperature sensitivity of soil organic carbon mineralization Q10 (30 °C/20 °C) had a direct but non-significant effect on CEM. The above findings suggest that R. typhina can generate positive feedback by influencing the physicochemical properties and CEM of the soil, opening the way for its own expansion, which can be targeted to prevent the destruction of local ecosystems during the introduction of cultivation and subsequent management.